PROMOSI POLA HIDUP SEHAT DAN MAKANAN BERGIZI PADA KELOMPOK RENTAN GIZI SELAMA PANDEMI COVID-19 DI KOTA PADANG - Azrimaidaliza Azrimaidaliza; Yasirly Khairany; Rahmi Putri; Arethusa Assyurrha Syara; Fransiska Waromi (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
The condition of the COVID-19 pandemic that has hit the world, including Indonesia, which can cause death, requires the public to take preventive measures. One of the efforts that can be made so as not to be exposed to COVID-19 is to increase a healthy lifestyle and consumption of nutritious food during the COVID-19 pandemic. The purpose of education is to improve healthy lifestyle and consume nutrtitious food for vulnerable groups. The targets of this activity is children under-fives, pregnant women, and the elderly as many as 17 targets who are in the working area of Pauh Puskesmas and Puskesmas Padang Pasir, Padang City. The method is carried out by means of counseling which begin by visiting the target house, which is then carried out through WhatsApp (WA) social media. In educational activities, service providers, through the media leaflets and posters that have been designed, are then conveyed directly to the service target and through social media, namely the WA group. Educational activities during the pandemic went quite well was followed by 17 mothers with children under five and elderly. This was shown with a quite high enthusiasm when the activity begins and some target asked the questions related to material that had not been understood and then answered by the service provider. Various efforts and strategies are needed from health workers so that educational activities can still be carried out for the community in breaking the chain of the spread of COVID-19.